Intellectual production of Amélia Americano Domingues de Castro (1920-2020): contribution to the theaching and Didactics of Geography - Márcia Cristina de Oliveira Mello (2022)
The following is a presentation of the intellectual production and thought of Professor Amélia Americano Domingues de Castro (1920-2020). The professor graduated and worked at the Faculty of Philosophy, Sciences and Letters (FFCL) of the University of São Paulo (USP), from 1942 until her retirement.  She stood out for introducing the ideas of Jean Piaget in the initial teacher training course in Geography and History at the time. The course was a pioneer in teacher training at a higher level in Brazil, where Amélia taught for the first time the discipline of Didactics of Geography. Thus, our research goal is to highlight the theoretical bases of her thought, pointing out, among her intellectual production, the studies that disseminated the bases that founded a way of thinking about teaching in the Human Sciences area, with emphasis on Geography. As a specialist in Didactics, Professor Amélia has been little noticed in the production about Geography teaching so far. Thus, we rescue this important fact for the history of the Geography school subject, fostering the debate about the teaching-learning process of geographic concepts, based on studies that point to the overcoming of the idealization of teaching methods in detriment of the psychological, cognitive, moral, social and cultural aspects of the teaching-learning process. In this sense, Professor Amélia left a legacy allied to the matrix characterized by the 20th century Piagetian orientation, which had countless variables, certainly replicated by her former students such as Aziz Ab'Sáber and Lívia de Oliveira. To conclude, the theoretical bases of Professor Amélia's thought constitute a legacy to the Didactics of Geography.